FRENCH LEARNING DIGITALIZATION SERVICE THROUGH THE DEVELOPMENT OF EDUCATIONAL GAMES - Destiara, Ria Fuji; Fibriasari, Hesti; Nasution, Rizki Fadila; Rahmadany, Savitri (Journal of Community Research and Service, 2024)
When applying your knowledge of a foreign language, it is crucial to adhere to ethical and respectable linguistic rules. Grammar and vocabulary are what require in language. Students will have an easier time learning foreign languages if they comprehend grammatical conventions and become fluent in their vocabulary because these skills are crucial for performing language acts. Language skills and the fundamental abilities of kids in speaking, listening, reading, and writing both include vocabulary. It is important to maximize vocabulary development when learning French at school. Therefore, more engaging instruction is required to increase vocabulary acquisition, complemented by the best possible use of technology as a learning medium. By providing French learning materials in the form of an educational Android game that teachers may use to master vocabulary, this hopes to digitize French instruction in schools and make it more engaging for kids.